A refinement of the relationship between central bank independence, inflation, and income inequality in developing countries - Fadi Fawaz; Masha Rahnamamoghadam (Journal of Central Banking Theory and Practice, 2024)
This paper analyzes the impact on income inequality of a set of variables usually considered in the growth literature as potential growth determinants. There is evidence to suggest that unemployment and inflation are positively associated with income inequality; except for countries with central bank independence where a negative association exists between inflation and income inequality. The empirical evidence shows that income inequality increases when unemployment increases.
Keywords: C13; C33; D31; 330; Central Bank Independence; Income Inequality; Developing Countries; Fixed Effects